2007
DOI: 10.1007/s11606-007-0273-6
|View full text |Cite
|
Sign up to set email alerts
|

Interest in the Use of Computerized Patient Portals: Role of the Provider–Patient Relationship

Abstract: BACKGROUND: Bioinformatics experts are developing interactive patient portals to help those living with diabetes and other chronic diseases to better manage their conditions. However, little is known about what influences patients' desires to use this technology. OBJECTIVE:To discern the impact of the providerpatient relationship on interest in using a web-based patient portal. DESIGN: Qualitative analysis of focus groups.PARTICIPANTS: Ten focus groups involving 39 patients (range 2-7) recruited from four prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 39 publications
(34 reference statements)
5
93
0
Order By: Relevance
“…29 A concern was raised that genetic test results appearing in the medical record in the absence of a carefully constructed interpretation have the potential for being misinterpreted resulting in undue alarm to and/or faulty decision-making by patients and their families. To minimize the potential for misunderstanding and promote patient understanding, workgroup participants suggested that patients or patient groups be consulted in developing or improving the format and wording of the result report and its presentation in the medical record.…”
Section: Discussionmentioning
confidence: 99%
“…29 A concern was raised that genetic test results appearing in the medical record in the absence of a carefully constructed interpretation have the potential for being misinterpreted resulting in undue alarm to and/or faulty decision-making by patients and their families. To minimize the potential for misunderstanding and promote patient understanding, workgroup participants suggested that patients or patient groups be consulted in developing or improving the format and wording of the result report and its presentation in the medical record.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some qualitative research has linked patient interest in portals with dissatisfaction with the patient-provider relationship. 18 In either case, provider attitude and behavior are likely to be key factors for future research.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Zickmund et al reported on a connection between patient dissatisfaction with the patient-provider relationship and increased interest in the use of PAEHR [23] . Two studies reported that users who logged in more frequently were of superior health status [18,27] , while a third reported contrary findings as the users in their study experienced more symptoms and had more visits with providers [15] .…”
Section: User Characteristicsmentioning
confidence: 99%
“…[15,20,36,31] . Several groups advocated for an edited version of the electronic medical record that provides explanatory information [15,23,29] or a glossary of medical terms [31] and is easier to understand for use by patients [15,24] .…”
Section: Barriers To Adoptionmentioning
confidence: 99%
See 1 more Smart Citation